Palaeoseismic investigations along the Kachchh Mainland Fault: A comprehensive review and new insights of the past earthquakes in the Kachchh basin, western India. (20th October 2021) - Kothyari, Girish Ch; Kandregula, Raj Sunil; Kotlia, Bahadur Singh; Lakhote, Abhishek; Swamy, K.V.; Pathak, Vamdev; Chauhan, Gaurav; Thakkar, M.G.
Abstract: The intraplate Kachchh Rift basin has been hit by several devastating earthquakes in the historic past including the 1819 Allah Bund Earthquake and the 2001 Bhuj earthquake. The source region of these earthquakes, within the basin have been studied by several workers in the last two decades to understand their potential for earthquake recurrence. However, very little information is available on the palaeoseismic and geomorphic characterization of Kachchh Mainland Fault (KMF). Therefore, in the present study, six trenches were excavated across the KMF, between Lakhpat and Nirona to understand ground deformation pattern and timing of the historic earthquakes. Based on geomorphic and palaeoseismic investigations, five palaeoearthquakes of Early to Late Holocene have been identified between 10, 000–890 yrs. Apart from the Holocene, an earthquake of Late Quaternary period was also identified, which possibly occurred around 19, 800 yrs BP. Fault related parameters were analyzed to understand the geometry of the active fault scarp along KMF. The results of the analyzed fault geometric parameters show that the vertical displacement along the KMF is higher than the horizontal displacement. The slip rate of the KMF from the western portion to the middle portion decreases from 0.08 to 0.04 mm/yr, and increases towards east from 0.22 mm/yr to 0.36 mm/yr. As the Kachchh district of the Gujarat state is rapidly developing in terms of infrastructural development, the outcome of this research might provide significant inputs for micro zonation studies and also in the evaluation of the seismic hazard in the Kachchh region.